Unlocking IP-backed financing series : country perspectives. (World Intellectual Property Organization, 2024)
"Luxembourg's Journey in the 'Unlocking IP-backed Financing Series' explores both current practices and the untapped potential of the SME ecosystem within Luxembourg. In particular, the report focuses on support for intellectual property (IP)-intensive companies. This report comes at a time when IP is increasingly attracting interest from rights holders, businesses, consumers and the general public."--